DAMPAK PERGESERAN WEWENANG PENGELOLAAN PERTAMBANGAN EMAS DI KABUPATEN KUANTAN SINGINGI PASCA UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Ridhola, Wisfika; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The writing of this thesis is based on the reality on the ground about the impact of the shift in the authority of gold mining management in Kuantan Singingi after the Law No. 23 of 2014 on Local Government. The purpose of this study is to find out how the Riau Provincial Government's authority in dealing with the problem of Unlicensed Gold Mining (PETI) in Kuantan Singingi Regency and How the Impact of Shifting Authority to Unlicensed Gold Mining in Kuantan Singingi After Law No. 23 of 2014 On Local Government. This research uses a qualitative approach. This type of research is descriptive research. The research location is Kuantan Singingi Regency. With the type of primary data, namely data obtained through interviews with informants related to research and secondary data, namely data obtained from reports, documentation, various books, the results of previous people's research regarding the Impact of Shifting Authority for Gold Mining without a Permit. Data collection techniques used interviews and documentation, then data analysis was, carried out using descriptive analysis with a qualitative approach. Based on the results of research and discussion, it can be concluded that the impact of the shift in gold mining authority in Kuantan Singingi Regency after Law Number 23 of 2014 concerning Regional Government is that the Regency and Provincial Governments do not have the authority to handle the issue of Gold Mining without a Permit. The Riau Province Energy and Mineral Resources Service, in collaboration with the Kuantan Singingi Regency Government, urges people not to carry out illegal mining. Keywords: Government Authority, Regional Government, and Gold Mining